Designing Animations in the Matter of Connection of Serial and Parallel of Batteries - Nigmet Koklu; Dundar Yener; Hamdi Sukur Kilic (International Journal of Applied Methods in Electronics and Computers, 2016)
When the research on physics teaching in universities is considered, some important investigations have been performed on the students' efforts to understand the physical world, but they unfortunately show that students could not understand the concepts as expected.   The development on the computer technology affecting the physical education significantly are became more important and consequently carrying out of computer aided physics education are inevitable.   Many scientific research articles have been reported about making education progress is more exciting and attractive.  One of the most impressive applications made on this issue is still computer animation.  Through computer animation, students’ grip for increased interest in the subject as well as the preparation of this animation style is drawn to stimulate their interest more easily. In this study, animations have been prepared for teaching series and parallel connection of batteries which is a part of general physics laboratory course. It is aimed that topic can be understood by students even faster, more comfortable and easier.  In the created animations, it has been shown how to connect the series and parallel circuits.  It is intended that topic has been reinforced by the students with the given samples and created graphics